An Empirical Analysis of Carbon Emissions in International Trade and Economic Growth for E7 Countries - Thangaiyarkarasi, N.; Vanitha, Selvaraj; Maniam, Balasundram; Srinivasan, P. (International Journal of Energy Economics and Policy, 2025)
This study investigates the relationships among Carbon Emissions (CO2), Energy Use (EU), Broad Money (BM), Renewable Energy Consumption (REC), Gross Domestic Product (GDP), Domestic Credit to the Private Sector (DCPS), and Imports (IMP) and Exports (EXP) in the E7 countries – Brazil, China, Indonesia, India, Mexico, Russia, and Turkey – using the stepwise least-squares method. By analysing panel data from 2009 to 2023, the research explores the short- and long-term impacts of economic growth, domestic credit to the private sector, and imports and exports on carbon emissions for E7 countries. The findings reveal that in the long run, the economic growth of GDP, imports and domestic credit to the private sector have significant positive effects on carbon emission, indicating that as an individual country's economic growth increases, it will increase its carbon emissions with the help of innovative technologies, industrialization, urbanization and renewable energy sources. The study concluded that the E7 Countries are emerging economies and also concentrate on decarbonization goals and strategies. With this E7 or emerging economies, China and India are the second and third-largest emitters in the world. The study suggests that the emerging countries should concentrate on economic growth for a green environment, Net-Zero goals and objectives, and follow the policies to attain carbon neutrality and net-zero carbon emission in the emerging economies.